The Influence of Service Quality on Customer Satisfaction Mediated by Customer Loyalty : (Study on Garnier Customers In Malang City) - Deva Nur Marifah; Rohmat Dwi Jatmiko; Sri Nastiti Andharini (Universitas Muhammadiyah Malang, 2022)
The purpose of this study is to describe and examine the effect of customer perceptions of Garnier service quality on customer satisfaction mediated by customer loyalty. The data analysis technique used path analysis. The results of this study indicate that service quality and customer loyalty has a positive and significant effect on Garnier’s customer satisfaction. The results of the analysis show that the customer's perception of the quality of Garnier can be seen in a good category. Garnier customer satisfaction is in the satisfied category. Garnier customer loyalty is in the loyal category. Service quality affects customer satisfaction, meaning that the better the quality of Garnier, the more customer satisfaction will increase. Customer satisfaction affects customer loyalty, meaning that with increasing customer satisfaction, customer loyalty will increase.